Sequential breakdown of the Cf-9 leaf mould resistance locus in tomato by Fulvia fulva. - de la Rosa S; Schol CR; Ramos Peregrina Á; Winter DJ; Hilgers AM; Maeda K; Iida Y; Tarallo M; Jia R; Beenen HG; Rocafort M; de Wit PJGM; et al. (John Wiley and Sons Ltd on behalf of New Phytologist Foundation, 2024)
Leaf mould, caused by Fulvia fulva, is a devastating disease of tomato plants. In many commercial tomato cultivars, resistance to this disease is governed by the Cf-9 locus, which encodes five paralogous receptor-like proteins. Two of these proteins confer resistance: Cf-9C recognises the previously identified F. fulva effector Avr9 and provides resistance during all plant growth stages, while Cf-9B recognises the yet-unidentified F. fulva effector Avr9B and provides mature plant resistance only. In recent years, F. fulva strains have emerged that can overcome the Cf-9 locus, with Cf-9C circumvented through Avr9 deletion. To understand how Cf-9B is circumvented, we set out to identify Avr9B. Comparative genomics, transient expression assays and gene complementation experiments were used to identify Avr9B, while gene sequencing was used to assess Avr9B allelic variation across a world-wide strain collection. A strict correlation between Avr9 deletion and resistance-breaking mutations in Avr9B was observed in strains recently collected from Cf-9 cultivars, whereas Avr9 deletion but no mutations in Avr9B were observed in older strains. This research showcases how F. fulva has evolved to sequentially break down the Cf-9 locus and stresses the urgent need for commercial tomato cultivars that carry novel, stacked resistance genes active against this pathogen.
Keywords: Avr9 and Avr9B avirulence effector genes; Cf‐9 locus; Cf‐9C and Cf‐9B resistance genes; Fulvia fulva (Cladosporium fulvum); Solanum lycopersicum (tomato); fungus; sequential resistance breakdown; tomato leaf mould disease